Association of bundled care interventions in improving outcomes for pediatric patients with congenital heart disease: a retrospective clinical evaluation - Zhang, Li; Song, Yu-Ting (Frontiers in Pediatrics, 2025)
BackgroundCongenital heart disease (CHD) in pediatric patients requires comprehensive care to address complex medical and psychological needs. Traditional approaches may lack the structure and coordination to optimize recovery fully. This study evaluates the association of Bundled Care Interventions, a structured multidisciplinary approach, in improving clinical outcomes and quality of life in pediatric CHD patients.Materials and methodsA retrospective evaluation was conducted at our hospital from January 2021 to December 2023. Pediatric patients (n = 136) under 14 years of age diagnosed with CHD were included, with 70 receiving Bundled Care Interventions (observation group) and 66 receiving conventional care (control group). The bundled care model included preoperative education, optimized intraoperative management, personalized postoperative rehabilitation, home-based care, and medication management. Primary outcome measures included oxygenation status, quality of life, adverse events, and complications. Statistical analyses were performed using independent t-tests and chi-square tests.ResultsPatients in the Bundled Care Interventions group showed significant improvements in oxygenation (PaO2 and FiO2; p < 0.001) and quality of life across all dimensions (p < 0.001) compared to the control group. Additionally, adverse event incidence was lower in the observation group (4.29% vs. 15.2%; p = 0.031), as was the incidence of postoperative complications (5.71% vs. 18.2%; p = 0.024).ConclusionsBundled Care Interventions might improve oxygenation levels, enhance quality of life, and reduce adverse events and complications in pediatric CHD patients. This structured, multidisciplinary approach could offer a promising model for optimizing clinical outcomes and supporting comprehensive rehabilitation in this vulnerable population.